A new revised and adapted key to Aureoboletus (Boletaceae) - Klofac, Wolfgang; Gelardi, Matteo (Phytotaxa, 2025)
The recent description of many new species in the genus Aureoboletus and the inclusion of several taxa from multiple different genera based on molecular phylogenetic knowledge makes it necessary to adapt and update the previous key from Klofac (2010). The present key relies on data from the literature. A new combination Aureoboletus belizensis is proposed and a new section Aureoboletellorum is described, based on morphology, microscopy and molecular phylogenetic evidence.